Family decision–making in emerging economies. (1st January 2015) - Chaudhary, Monica
The purpose of this paper is to examine the children's role in family decision–making in emerging economies. Using a structured questionnaire, a survey was conducted with 175 children from India. The results revealed that children across cultures have high influence over family purchase decisions. Moreover, consistent with the ranking of India as a culturally high power distance nation, Indian children had lower influence than their Turkish counterparts. The findings of the study have interesting implications for global marketing practitioners. As Indian parents are more authoritative than US and Turkish parents, marketers need to keep in mind that they do need to appeal to children as much as they may need to appeal to parents. This paper contributes to the extant literature available in the area of family's decision–making. This study holds its importance as it provides detailed and insightful comparisons between two emerging markets.